In vivo parcellation of the human superior colliculus from brain-wide probabilistic connectivity - Matteo Diano; Carlos Andrés Méndez; Olga Dal Monte; Marco Lanzilotto; Davide Orsenigo; Alessio Borriero; Enrico Premi; Alessia Celeghin; Matteo Panormita; Luca Bonini; Giuseppe Di Cesare; Marzio Gerbella; et al. (Proceedings of the National Academy of Sciences, 2025)
The Superior Colliculus (SC) is a multimodal integration midbrain structure receiving input from various sensory systems (visual, auditory, and somatosensory) and using this information to guide rapid, reflexive responses. Research using invasive animal model techniques has extensively characterized the SC connectional fingerprint and subcomponent differentiation. However, the extent to which these findings can be generalized to humans remains largely unknown. Here, we developed a fully data-driven approach to examine the wiring diagram of each voxel in the human SC in a cohort of 200 participants. Using diffusion MRI to infer probabilistic tractography, we identified three subregions within the human SC with distinct topography and unique brain-wide connectivity patterns. A superficial division is primarily linked with visual cortical areas, the amygdala, and the posterior thalamus. An intermediate-lateral division is connected predominantly with the auditory and somatosensory cortices and with sectors of the posterior parietal cortex. A deep subregion exhibits preferential connectivity with the brainstem and cerebellum. These in vivo features highlight the heterogeneity in the extrinsic connectivity of the human SC. Probabilistic coupling partly reflects conserved SC interaction motifs reported in other mammals with direct tracing methods, while also showing potential adaptations of cortical–midbrain interactions compatible with human neocortical expansion.